2019
DOI: 10.1002/ctpp.201900032
|View full text |Cite
|
Sign up to set email alerts
|

The role of second‐order radial density gradient for helicon power absorption

Abstract: To demonstrate the mysterious and still controversial mechanism of high ionization efficiency during helicon discharges, this work focuses particularly on the role of second‐order radial density gradient (SRDG) in helicon power absorption, both analytical and numerical. It was found that the positive or negative sign of SRDG and radial location of vanishing SRDG determine the radial profile of power absorption remarkably. First, by measuring SRDG at two radial locations (near plasma core and edge) where power … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
3
1
0
Order By: Relevance
“…This is consistent with the experimental observation that the discharge transits from blue-colour mode to blue-core mode [9]. The decreased power for shrunk density profiles implies that certain magnitude of plasma density near edge is beneficial for power coupling, which also agrees with previous studies [40,41,42,43,44]. More interestingly, we find that the power deposition is hollow in radius for all field strengths and its peak moves closer to axis when the field strength increases.…”
Section: Power Depositionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the experimental observation that the discharge transits from blue-colour mode to blue-core mode [9]. The decreased power for shrunk density profiles implies that certain magnitude of plasma density near edge is beneficial for power coupling, which also agrees with previous studies [40,41,42,43,44]. More interestingly, we find that the power deposition is hollow in radius for all field strengths and its peak moves closer to axis when the field strength increases.…”
Section: Power Depositionsupporting
confidence: 92%
“…This could be attributed to the plasma density near edge which is too low to efficiently couple the power from antenna into core. This critical role of edge density has been also claimed by other studies [40,41,42,43,44].…”
Section: Step-like Function Theorysupporting
confidence: 81%
“…It is commented that (a-c) are generic phenomena for plasma discharge and insufficient to support the remarkable ionisation rate and high density of helicon sources, and more attention should be paid to (d-e) which involves the critical parameter of confining magnetic field that promotes the density jump from inductively coupled plasma to helicon mode; further, (4) and ( 5) rely on density magnitude and density gradient, respectively, and optimum discharge may be achieved when the required density magnitude comes across with the largest density gradient at the same location. Then, the sign (positive or negative) and zero-crossing position of second-order density gradient are shown to effect the power absorption profile significantly, consistent with (5) [32][33][34]. Moreover, it is suggested that the power deposition profile could be shaped by designing the antenna of particular geometry to excite the required axial current distribution, considering their resemblance.…”
Section: Introductionsupporting
confidence: 54%
“…In this paper, the influence of temperature and pressure gradients on power deposition, electric field intensity, and current density under two different plasma density distributions is studied by using HELIC code. [21][22][23] Compared with other codes (such as EMS code, ANTENA2 code, SPIREs code, ANAMANT code), HELIC code uses specific boundary conditions to solve six radially coupled differential equations to obtain two independent waves (H wave and TG wave). It is much faster than dividing the nonuniform plasma into layers and matching boundary conditions on each interface.…”
Section: Introductionmentioning
confidence: 99%